North Slope Borough Commission on History and Culture, Kaktovik, Alaska An Overview of Relocations - Nelson, Jon M.; Frankson, Ernie; Brower, Ronald; Maldo Bodfish; Morry, Amos; Woods, Nanny; Neakok, Warren (1977)
This study attempts to assess the past and present relationships between the United States Navy, the United States Air Force, and the Northern Eskimo village of Kaktovik, Alaska. Specifically, it focuses on the question of Arctic military land withdrawals: how these withdrawals were established, which priorities were involved and what their impact has been upon this village in terms of community development and planning.